Clinical - epidemiological profile of people with bipolar disorder in psychiatric hospitalization (Research, Society and Development, 2020)
Introduction: Bipolar disorder is a change in mood that varies from a state of major depression to extreme euphoria (hypomania and mania), separated by periods of stability. However, there are cases where psychiatric hospitalization is necessary, after all extra-hospital resources are exhausted. Objective: To identify the clinical-epidemiological profile of people with bipolar disorder in psychiatric hospitalization. Methodology: Documentary, retrospective, quantitative analysis, developed in a Mental Health hospital in Fortaleza-Ceará, between March and July 2017. Data were collected from the medical records of patients hospitalized between January and August 2016 diagnosed with bipolar disorder by a previously elaborated instrument, analyzed using simple descriptive statistics and discussed based on the relevant literature. Results and Discussions: 100 records were analyzed, observing the majority profile of women (70%), single (61%), aged between 26 and 35 years (28%) and with elementary education (43%); 86% of admissions were involuntary, motivated by own life attempt (37%) and the nursing consultation identified insomnia, disorientation and auditory hallucination as the main alterations. Hospitalizations had an average duration of 16 to 30 days and the most used drugs in this period were haloperidol, combined with promethazine, and lithium. After discharge, 95% of patients were referred to Psychosocial Care Centers. Conclusion: Bipolar disorder is a chronic disease that requires individualized care to preventing new hospitalizations and promoting mental health in its continuum.